Islamic Views on Online Shopping - Apriyani, Nur (Jurnal Iqtisaduna, 2023)
Sale and purchase is an agreement to exchange goods/services that have value, between 2 parties with agreements/conditions justified by syara’. Shari’a means that buying and selling is tried in accordance with the terms, pillars and other matters related to buying and selling. Humans as social beings who live together need one another, hikmah from buying and selling can help humans for this qualitative survival. This study uses a literature research study through novels, diaries and other literature to form a theoretical basis. To examine written sources such as scientific diaries, literature reference novels, encyclopedias, scientific essays, scientific papers and other sources both in writing and in digital formats that are relevant to the object being researched either in the form of text or writing as well as to describe the online shop. Buying and selling in essence is not only consumptive in nature and only has material factors to gain profit in this world, but also essential benefits in the hereafter, of course by paying close attention to the principles of buying and selling which are permissible according to syar’i. At present, business models are emerging using modern technological sophistication. With the development of electronics, it influences aspects of human life, especially in online buying and selling transactions, namely the internet. Technological growth makes it easier for someone to access the internet. This convenience is utilized in fulfilling all daily needs as well as buying and selling transactions of goods or services via the internet/online. Online transactions are the same as offline, which distinguishes the place for transactions in cyberspace, even though they are in different regions. Buying and selling online is permissible if it matches the requirements of Islam. As long as no one is harmed and agrees, buying and selling online is allowed.